Exposure to several polychlorinated biphenyls (PCBs) is associated with chronic kidney disease among general adults: Korean National Environmental Health Survey (KoNEHS) 2015–2017. (September 2022) - Lee, Jeonghwan; Lee, Inae; Park, Jae Yoon; Kim, Sunmi; Park, Hyunwoong; Jung, Sun Kyoung; Lee, Chulwoo; Lee, Jung Pyo; Choi, Kyungho
Abstract: We investigated the association between major persistent organic pollutants (POPs) exposure and chronic kidney disease (CKD) among general adult population of Korea. For this purpose, a subset of the adult population (n = 1276) participated in Korean National Environmental Health Survey (KoNEHS) Cycle 3 (2015–2017) were analyzed for twenty-four POPs in serum, including organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs), and were derived for estimated glomerular filtration rate (eGFR) and urinary albumin-to-creatinine ratio (uACR). Multivariable linear regression was conducted to assess the association between POPs exposure and CKD-related parameters including eGFR and uACR. As sensitivity analyses, principal component analysis was conducted. Moreover, the U.S. National Health and Nutrition Examination Survey (NHANES) 1999–2004 data were chosen to compare with the observations of the Korean adults. Approximately 7.7% of the Korean adult population possessed CKD based on either eGFR (<60 ml/min/1.73 m 2 ) or uACR (≥30 mg/g) criteria. Among the POPs that were detected in ≥70% of the subjects, PCB153 (β = −1.61, 95% CI: −2.55, −0.67, P = 0.001) and PCB180 (β = −1.47, 95% CI: −2.53, −0.40, P = 0.007) exhibited significant associations with decreased eGFR, especially in females. In male participants, hexachlorobenzene (HCB) was associated with eGFR (β = −0.79, 95% CI: −1.53, −0.04, P = 0.040). Sex-dependent associations with eGFR were also shown in the PCA model. Moreover, the sex-dependent associations of PCBs were similarly observed in the adult populations of the US NHANES. However, POPs exposure was not associated with uACR, regardless of association model or population. The observed associations of PCBs are supported by several experimental studies reported elsewhere. To our knowledge, it is the first report that suggests significant associations of PCBs and HCB with eGFR among general population, and further validations in other populations are warranted. Graphical abstract: Image 1 Highlights: Major POPs and CKD parameters were associated in a general adult population. A subset of KoNEHS Cycle 3 was randomly selected after age and sex stratification. Serum PCB153 and 180 were associated with reduced eGFR. For PCB153, 180, and HCB, sex-dependent associations with eGFR were observed. Similar associations were found in the US adults participated in NHANES 1999–2016.